Demonstration of biological activity of brain gastrin-like peptidic material in the human: its relationship with the COOH-terminal octapeptide of cholecystokinin. - Robberecht, P (1978)
The previously described peptide material that reacts with antibodies to gastrin and is found in the central nervous system of various vertebrates is present in only the 100,000 X g pellet of postmortem human cerebral cortical grey matter. This immunoreactive material, extractable in boiling water, is biologically active on rat pancreatic preparations. On the basis of size, charge, immunological specificity, and patterns of biological activity, most of this material is closely related to the COOH-terminal octapeptide of cholecystokinin in its complete, sulfated biologically active form.